PENGUATAN BADAN PENGAWAS PEMILU DALAM PROSES PENEGAKAN HUKUM PEMILU - Rosidin, Utang (Bawaslu Provinsi Jawa Barat, 2023)
The 2019 general election is considered a complex election in terms of organization and types of violations. Allegations of election violations prompted changes in the various laws governing them. In preparation for the 2024 election, the General Election Supervisory Agency (Bawaslu) is working to strengthen election laws. This includes improving enforcement institutions and establishing Bawaslu as a permanent institution. Additionally, they are addressing the increasingly complex types of violations and the severity of sanctions. A normative-legal approach is the research methodology employed in this study. The study found that Bawaslu addressed election violations in two ways: settling election administrative violations through an open hearing conducted by the examining panel and settling election administrative violations through a fast event, in accordance with Law Number 7 Year 2017 on General Elections, which specifically refers to Perbawaslu Number 7 Year 2022 on Handling Election Violation Findings and Reports, Perbawaslu Number 8 Year 2022 on Completion of General Election Administrative Violations, and Perbawaslu Number 3 Year 2023 on Integrated Law Enforcement Center.